Horizontal and vertical maxillary osteotomy stability, in cleft lip and palate patients, using allogeneic bone graft - Kelston Ulbricht Gomes; Wilson Denis Benato Martins; Marina de Oliveira Ribas (Dental Press Editora, 2013)
OBJECTIVE: This study was carried out to evaluate maxillary stability after orthodontic-surgical treatment of patients with cleft lip and palate. Cephalometric analysis was applied to two different groups, with and without allogeneic bone graft. METHODS: The sample comprised 48 patients with cleft lip and palate. The test group comprised 25 patients who, after correction of maxillary position, received allogeneic bone graft at the gap created by Le Fort I osteotomy. The control group comprised 23 patients and its surgical procedures were similar to those applied to the test group, except for the use of bone graft. Manual cephalometric analysis and comparison between lateral teleradiographs, obtained at the preoperative phase, immediate postoperative phase and after a minimum period of six months, were carried out. RESULTS: An higher horizontal relapse was observed in the control group (p<0.05). There were no statistically significant differences in vertical relapses between test and control groups (p>0.05). CONCLUSION: The use of allogeneic bone graft in cleft lip and palate patients submitted to Le Fort I osteotomy contributed to increase postoperative stability when compared to surgeries without bone graft.